Economics of fish production in paddy fields in Bangladesh - Rahman, Hafzur; Mirza, Jabed Ali; Hossain, Amir; Asif, Abdulla Al; Haq, Emdadul; Chwakravorty, Palas; Rahman, Mizanur (Asian Journal of Medical and Biological Research, 2017)
This study was conducted to assess profitability of fish production in paddy fields in the village of Kunia and Chandora, under Gacha union in Gazipur sadar upazila in Gazipur district. Primary data were collected from 15 fish farmers for the study during the period from June to November, 2016. Production performance of three stocking package were compared. CFP-1 package contained Thai sarpunti (24700/ha) + Tilapia (6175/ha); CFP-2 comprised of Thai sarpunti (24700/ha) + Common carp (6175/ha); while CFP-3 was represented by Thai sarpunti (24700/ha) + (Tilapia (6175/ha) + Common carp (6175/ha). Both tabular and functional analyses were used to achieve the objectives of the study. Fish productions in paddy fields are profitable business. The total cost of fish production under three selected stocking plans such as CFP-1, CFP-2 and CFP-3 were estimated to be Tk. 73085, Tk. 83459 and Tk. 86928 per ha, respectively. The corresponding total gross return (Tk./ha) were Tk. 209777, Tk. 274170 and Tk. 262721, respectively. The benefit cost ratio (BCR) was estimated to be 2.87, 3.28 and 3.02 for package-1, package-2 and package-3, respectively. Returns over per taka investment (NR/Tk.) were found to be 1.32, 1.69 and 1.42 for the above fish culture packages. Cobb-Douglas production function analysis indicated the positive contribution of fish fingerlings, fertilizer, fish feed and lime on the total income and farm productivity, while human labor and bank interest rate decreased the farm income. The values of R2 were 0.775, 0.739 and 0.812 for CFP-1, CFP-2 and CFP-3, respectively. About 77.5 percent, 73.9 percent and 81.2 percent of variation in yield and gross return of fish production in paddy fields could be explained by the multiple regression equations. Fish production in paddy fields are economically profitable, viable and environment friendly. The farmers may undertake fish culture in paddy fields if suitable paddy fields are available. Asian J. Med. Biol. Res. September 2017, 3(3): 379-390